Seizure - Reichs, Kathy (Reichs, Kathy. Virals novel., 2011)
Ever since Tory Brennan and her friends rescued Cooper, a kidnapped wolf pup with a rare strain of canine parvovirus, they've turned from regular kids into a crime-solving pack! But now the very place that brought them together - the Loggerhead Island Research Institute - is out of funding and will have to shut down. That is, unless the Virals can figure out a way to save it!